2013
DOI: 10.1371/journal.pone.0062304
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of CD26 Induced by a Humanized Monoclonal Antibody Inhibits Tumor Cell Growth by Modulating of POLR2A Transcription

Abstract: CD26 is a type II glycoprotein known as dipeptidyl peptidase IV and has been identified as one of the cell surface markers associated with various types of cancers and a subset of cancer stem cells. Recent studies have suggested that CD26 expression is involved in tumor growth, tumor invasion, and metastasis. The CD26 is shown in an extensive intracellular distribution, ranging from the cell surface to the nucleus. We have previously showed that the humanized anti-CD26 monoclonal antibody (mAb), YS110, exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 46 publications
(71 reference statements)
0
43
0
Order By: Relevance
“…however, in contrast to DPP9, analysis of the DPP8 sequence with the cNLS mapper program does not predict an NLS at the amino terminus of the protein but instead a putative bipartite NLS in all DPP8 isoforms (data not shown). Previously, DPPIV was also reported to localize to the nucleus in human cancer cells such as cultured malignant t cell lines [47,48]. this translocation however is different from that observed for DPP9, and presumably does not involve an NLS, but instead caveolin-dependent endocytosis of DPPIV and a yet not further analyzed mechanism into the nucleus.…”
Section: Dpp9-l Is An Active Peptidasementioning
confidence: 75%
See 1 more Smart Citation
“…however, in contrast to DPP9, analysis of the DPP8 sequence with the cNLS mapper program does not predict an NLS at the amino terminus of the protein but instead a putative bipartite NLS in all DPP8 isoforms (data not shown). Previously, DPPIV was also reported to localize to the nucleus in human cancer cells such as cultured malignant t cell lines [47,48]. this translocation however is different from that observed for DPP9, and presumably does not involve an NLS, but instead caveolin-dependent endocytosis of DPPIV and a yet not further analyzed mechanism into the nucleus.…”
Section: Dpp9-l Is An Active Peptidasementioning
confidence: 75%
“…the reduced efficiency of the inhibitor probably leads to an underestimation of the DPP8&9 prolyl peptidase activity in the nucleus. Moreover, in contrast to malignant t cell lines [47,48], Western-blot analysis of heLa nuclear fractions suggests that DPPIV does not contribute to the major DPP activity in this fraction. thus, although we cannot exclude that other unknown enzymes may contribute to prolyl peptidase activity in the nucleus, our results show for the first time the nuclear localization and activity of DPP9 (and DPP8) in this compartment.…”
Section: Dpp9-l Is An Active Peptidasementioning
confidence: 82%
“…Similar to sMET, sCD26 originates from the shedding of surface-bound CD26. Overexpression of DPP4 is observed in various human cancers, including thyroid, breast, prostate, and ovarian cancers and is involved in tumor development, invasion, and metastasis (60,61). However, previous studies have also observed that sCD26 was deficient in total homogenates of colon, kidney, lung, and liver tumors (62,63) as well as in different transformed and cancer-derived cell lines (64).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a CD26/DPP4 antibody was employed as a therapeutic measure in mesothelioma and T-cell lymphoma showing down-regulation of RPB1 followed by inhibitory DNA binding of CD26/DPP4 [16][17][18]. In a rat study, the effect of CD26/DPP4-inhibition on colon carcinogenesis was shown by a long term treatment with the CD26/DPP4-inhibitor Sitagliptin [19].…”
Section: Introductionmentioning
confidence: 99%